Management of the Post-COVID Condition with Ashtadashanga Churna (Poly herbal Ayurveda medicine) - Reddy, Prof. K. Rama Chandra (Asian Journal of Pharmaceutics (AJP), 2024)
Ethnic Pharmacological Relevance: The post-COVID sequel in COVID 19 survivors led to a new strain on health-care professionals at the end of the pandemic. Although the pathogenesis of which is not fully understood symptoms that are mostly seen in post-COVID sequel are fatigue, shortness of breath or difficulty in breathing, loss of memory and concentration, sleep problems, persistent cough, chest pain, trouble speaking, muscle ache, loss of smell or taste, depression or anxiety, fever, decrease quality of life, and olfactory and gustatory dysfunction. Ashatadashanga Churna (AC) an Ayurvedic polyherbal formulation is taken into consideration for targeting these post-COVID sequelae. Aim of this Review: Ashtadashanga churna can be a potent drug in the treatment of post- COVID sequela classical polyherbal formulation mentioned in the Yogratnakara textbook under the jwara (fever) chapter, one of the authoritative Ayurvedic textbooks. It contains 18 herbal drugs. Each drug of the formulation as an individual and whole formulation is studied to provide a comprehensive insight into its action on post- COVID sequelae and general health improvement. Materials and Methods: To examine the impact of each ingredient on post-COVID symptoms, we compiled the information for this article using electronic searches utilizing PubMed, Google Scholar, and Web of Science. Results: This medicine’s different probable modes of action are scavenging free radical species, inhibiting inflammatory markers, immunomodulation, and protective effect. It is found to be indicated in similar signs and symptoms which is taken into consideration. It is found that all contents contribute to treating disease either individually or in a synergistic way. Conclusion: AC medicines may be potential as supplements or substitutes for treating post-COVID sequelae and for improvement of health. Ashtadashanga churna can be a potent drug in the treatment of post-COVID sequel so further research is needed in this formulation.